Determination of phosphorus in water using iron hydroxide assisted laser-induced breakdown spectroscopy. Issue 3 (19th January 2023) - Shao, Yang; Ma, Shixiang; Zhao, Xiande; Tian, Hongwu; Chen, Senliu; Dong, Daming; Zhou, Jianjun
Abstract : Phosphorus (P) in water could be selectively detected using iron hydroxide assisted laser-induced breakdown spectroscopy. Abstract : Phosphorus (P) is an important indicator for evaluating eutrophication in water bodies. Laser-induced breakdown spectroscopy (LIBS), as a total elemental analysis technique, is widely used in various fields. This work proposes a new application for this technique based on the adsorption of P using iron hydroxide. Using this method, a calibration curve with an R 2 of 0.996 was obtained along with an optimal limit of detection (LoD) of P in water of 0.1 mg L −1 . The analysis of spiked river and pond water samples showed P recoveries ranging from 94% to 113%. This adsorption-based analytical method of P allows the highly accurate assessment of actual water samples and could have practical applications.